The Climbing Drum Peel Test: An alternative to the Double Cantilever Beam for the determination of fracture toughness of monolithic laminates. (November 2015) - Daghia, F.; Cluzel, C.
Abstract: The experimental determination of the fracture toughness of inter-ply interfaces in monolithic composite specimens is far from trivial: even in standard test methods such as the Double Cantilever Beam (DCB), some precautions must be taken in the choice of the test configurations and in the post-treatment of the experimental results. Furthermore, non standard measurements such as the crack tip position during propagation are generally required. In this paper, we investigate an alternative test configuration, the Climbing Drum Peel (CDP) test, classically used in the 'adhesives' community. The adaptation of the CDP specimen configurations to the testing of monolithic composites is discussed and a systematic comparison is carried out between the CDP and the DCB tests in terms of global and local indicators of the crack propagation behavior.